2020
DOI: 10.1007/s00429-020-02081-y
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of transcranial direct current stimulation of left and right inferior frontal gyrus on creative divergent thinking are moderated by changes in inhibition control

Abstract: Divergent thinking (DT) as one component of creativity is the ability to search for multiple solutions to a single problem and is reliably tested with the Alternative Uses Task (AUT). DT depends on activity in the inferior frontal gyrus (IFG), a prefrontal region that has also been associated with inhibitory control (IC). Experimentally manipulating IC through transcranial direct current stimulation (tDCS) led to alterations in DT. Here, we aimed at further examining such potential mediating effects of IC on D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 74 publications
3
30
1
Order By: Relevance
“…Based on the outcomes of this study, it is clear that there is no singular measure that is sufficient to fully predict originality scores for a Design Product Ideation task. Despite the heavy reliance on AUT in creativity research, including in cognitive neuroscience studies of creativity [ 62 64 ], the present study found that although AUT originality was predictive of Design Product Ideation performance at pre-test, it was not significantly predictive at post-test when other predictive factors were included in a multiple regression model. In contrast, FIQ originality was predictive of Design Product Ideation originality at both pre- and post-test.…”
Section: Discussioncontrasting
confidence: 76%
“…Based on the outcomes of this study, it is clear that there is no singular measure that is sufficient to fully predict originality scores for a Design Product Ideation task. Despite the heavy reliance on AUT in creativity research, including in cognitive neuroscience studies of creativity [ 62 64 ], the present study found that although AUT originality was predictive of Design Product Ideation performance at pre-test, it was not significantly predictive at post-test when other predictive factors were included in a multiple regression model. In contrast, FIQ originality was predictive of Design Product Ideation originality at both pre- and post-test.…”
Section: Discussioncontrasting
confidence: 76%
“…On the other hand, INS inferior frontal areas did not differ between conditions and was neither increased in free play nor the proximate watching condition. The many functions associated with inferior frontal areas, such as language, inhibition and empathy, make it difficult pinpoint as to why mother-infant dyads did not show neural synchronization in that area (Khalil, Karim, Kondinska, & Godde, 2020;Shamay-Tsoory, Aharon-Peretz, & Perry, 2009;Wang, Yang, Zhao, Zuo, & Tan, 2020). It seems that INS in the IFG as part of the social interaction network proposed by Redcay and Schilbach (Redcay & Schilbach, 2019) was not yet synchronized during these early caregiver-infant interactions.…”
Section: Discussionmentioning
confidence: 99%
“…For left anodal stimulation, the anode was placed on F7 and the cathode on F8 and for right anodal stimulation, vice versa. The placement of electrodes was chosen as such because, in this position, frontal brain areas are stimulated well without spreading too much to other cortical areas [ 18 , 19 ]. We preferred this montage primarily to keep more posterior areas out of stimulation since the neuro-computational model [ 8 ] also includes the basal ganglia, thalamus, and motor areas.…”
Section: Methodsmentioning
confidence: 99%